A carbon rod with high COD removal life and preparation method thereof

By using ultra-high molecular weight polyethylene and low-density polyethylene as binders in activated carbon rod filter materials, combining activated carbon and mesoporous materials, the problem that activated carbon rod filter materials in the prior art cannot effectively remove COD in water during long-term use, and achieve efficient COD removal and extended service life.

CN119746814APending Publication Date: 2025-04-04FOSHAN XINYAO ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820426.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing activated carbon rod filter material cannot effectively remove COD from water throughout the entire process during long-term use, resulting in poor removal effect.

Method used

Ultra-high molecular weight polyethylene and low-density polyethylene are used as binders, combined with activated carbon and mesoporous materials, and carbon rods with high COD removal life are prepared through specific mixing and sintering processes.

Benefits of technology

It improves the filtration effect and removal life of carbon rods on small and large molecular pollutants in water, ensures effective removal of COD, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746814A_ABST
    Figure CN119746814A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of water purification materials, and specifically relates to a carbon rod with a high COD removal life and a preparation method thereof. The carbon rod comprises the following components, measured by mass, 10-35 parts of ultra-high molecular weight polyethylene, 5-20 parts of low-density polyethylene, 25-75 parts of activated carbon, 5-25 parts of mesoporous material and 0.1-3 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water purification materials, and in particular relates to a carbon rod with a long COD removal life and a preparation method thereof. Background Art

[0002] As people's requirements for drinking water quality continue to increase, consumers will re-purify municipal tap water for reuse. In the household water treatment industry, activated carbon rod filter material (CTO) is recognized and selected by many manufacturers because of its excellent adsorption capacity, which can effectively remove pollutants such as residual chlorine (Chlorine), odor (Taste), and organic matter (COD) in water. Especially in water purifiers, activated carbon rod filter material is often the filter material of the previous pretreatment process of reverse osmosis membrane elements. In the prior art, activated carbon rod filter material is preferably prepared by coconut shell activated carbon powder as raw material, which maintains a good removal rate and a long removal life for residual chlorine. However, for the treatment of organic matter (COD), the activated carbon rod filter material on the market cannot currently maintain a qualified removal rate (≥25%) throughout the entire life. When it removes COD in water for a long time, the problem of poor removal effect will occur. Even if better quality coconut shell activated carbon powder is used as raw material, it can only improve the initial removal rate of COD, which has little effect on the qualified life of COD removal rate.

[0003] Therefore, it is necessary to develop activated carbon rod filter materials with longer service life for COD removal. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a carbon rod with a long COD removal life and a preparation method thereof.

[0005] The present invention provides a carbon rod with a long COD removal life, which comprises the following components, measured by mass, 10-35 parts of ultra-high molecular weight polyethylene, 5-20 parts of low-density polyethylene, 25-75 parts of activated carbon, 5-25 parts of mesoporous materials and 0.1-3 parts of pore-forming agents, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

[0006] Preferably, the following components are included, by mass: 15-30 parts of ultra-high molecular weight polyethylene, 10-15 parts of low-density polyethylene, 30-70 parts of activated carbon, 10-20 parts of mesoporous material and 0.1-2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

[0007] Preferably, the viscosity of the ultra-high molecular weight polyethylene is 1500 mL / g to 3500 mL / g, and the melt index of the low density polyethylene is 0.1 g / 10 min to 5 g / 10 min.

[0008] Preferably, the iodine value of the activated carbon is greater than or equal to 900, and the particle size of the activated carbon is 80 mesh-325 mesh.

[0009] Preferably, the activated carbon is one or more of coconut shell activated carbon, bamboo activated carbon, fruit shell wood activated carbon, and biomass activated carbon.

[0010] Preferably, the particle size of the mesoporous material is greater than or equal to 200 mesh, the methylene blue value is greater than or equal to 8 mL / g, and the mesopore volume of the mesoporous material accounts for 40%-80% of the total pore volume.

[0011] Preferably, the mesoporous material is one or more of wood activated carbon, zeolite powder, molecular sieve, and diatomaceous earth.

[0012] Preferably, the pore-forming agent is hydroxyapatite or ammonium bicarbonate; or a mixture of hydroxyapatite and ammonium bicarbonate in a ratio of (1-3):1.

[0013] The present invention also provides a method for preparing a carbon rod with a long COD removal life, which is used to prepare the carbon rod with a long COD removal life as described in any one of the above items, and is characterized in that it comprises the following steps:

[0014] Step S1: low-density polyethylene and mesoporous material are mixed in proportion, placed in a stirrer and stirred for 5-60 minutes, heated to 20° C.-80° C., and stirred at a speed of 150-500 r / min to obtain a mixed material A;

[0015] Step S2: mixing ultra-high molecular weight polyethylene and activated carbon in proportion, placing in a stirrer and stirring for 5-60 minutes at a stirring speed of 150-500 r / min to obtain a mixed material B;

[0016] Step S3: Mixing the mixed material A and the mixed material B, placing them in a stirrer and stirring them for 5-60 min at a stirring speed of 150-500 r / min to obtain a carbon rod mixed material;

[0017] Step S4: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 100° C.-350° C. for 30 min-3 h, and cool it to room temperature after baking;

[0018] Step S5: demoulding and taking out the carbon rod, and cutting it into required size.

[0019] Preferably, before the mixing step of step S1 and step S2, the ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material are pre-dried, and the pre-drying process includes the following steps:

[0020] Step S10: placing ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material in containers of a drying device respectively;

[0021] Step S11: Start the drying equipment, the drying temperature is 50°C-150°C, the drying time is 2-5h, and the drying is completed and cooled to room temperature.

[0022] The carbon rod with high COD removal life and the preparation method thereof provided by the present invention have at least the following beneficial effects:

[0023] 1. The carbon rod of the present invention adopts a combination of activated carbon and mesoporous material, and uses ultra-high molecular weight polyethylene and low-density polyethylene as binders respectively, so that the combination of activated carbon and mesoporous material can be well combined together during sintering, so that the carbon rod has developed micropores and good mesopore volume, ensuring the excellent filtering effect and removal life of the carbon rod for small and large molecular pollutants in water.

[0024] 2. The preparation method of the present invention adopts a method of first mixing activated carbon and ultra-high molecular weight polyethylene, mesoporous material and low-density polyethylene in steps and then merging and mixing them together, which can well improve the distribution of each component material, and enhance the adhesion between ultra-high molecular weight polyethylene and activated carbon, and between low-density polyethylene and mesoporous material, which is manifested in that the overall strength of the sintered carbon rod is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and other purposes, features and advantages of the present invention will become more clear by more specific description of the preferred embodiments of the present invention shown in the accompanying drawings. The same reference numerals indicate the same parts in all the accompanying drawings, and the accompanying drawings are not deliberately scaled to the actual size, and the focus is on illustrating the main purpose of the present invention.

[0026] Figure 1 A schematic flow chart of a method for preparing a carbon rod with a long COD removal life is provided for an embodiment of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0028] Conventional activated carbon rod filter materials use coconut shell activated carbon with a well-developed surface microporous structure as raw material, which makes it have good removal efficiency and removal life when removing small molecules such as residual chlorine. However, when the influent pollutants are mainly large molecular organic matter, its surface micropores will soon be blocked, and the apparent manifestation is the failure of filtration performance. The reason is that activated carbon rod filter materials mainly remove large molecular organic matter by physical adsorption. It only adsorbs organic matter into it and cannot degrade organic matter. When its surface microporous structure is blocked, it will not be able to adsorb organic matter or release the adsorbed organic matter into the water again.

[0029] The present invention provides a carbon rod with a long COD removal life, which comprises the following components, measured by mass, 10-35 parts of ultra-high molecular weight polyethylene, 5-20 parts of low-density polyethylene, 25-75 parts of activated carbon, 5-25 parts of mesoporous materials and 0.1-3 parts of pore-forming agents, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

[0030] Ultra-high molecular weight polyethylene (UHMWPE) refers to polyethylene with a linear structure of relative molecular mass above 1.5 million. Ultra-high molecular weight polyethylene material has excellent flushing resistance, wear resistance, chemical corrosion resistance and self-lubricating properties, so it is a preferred material for making a binder for a tightly structured carbon rod, but the particle size of the ultra-high molecular weight polyethylene material is quite different from that of other mesoporous materials, resulting in poor adhesion, so the ultra-high molecular weight polyethylene material will not be used to prepare an activated carbon rod with a high porous structure, and the carbon rod directly prepared by it often cannot be formed when directly sintered. The present invention adopts a formula of ultra-high molecular weight polyethylene and low-density polyethylene for matching, and the low-density polyethylene has balanced physical properties, can melt at a lower temperature, has low process requirements and good chemical resistance, low-particle-size low-density polyethylene is contacted and mixed with a high-mesh mesoporous material in proportion, and ultra-high molecular weight polyethylene is mixed with activated carbon in proportion, and then the next step of mixing and sintering of the two is carried out, which can well improve the distribution of each component material, improve the adhesion between the binder and the adsorbent material, and the overall strength of the sintered carbon rod is high, and the hygienic and safety performance can also meet the standards. In addition, the carbon rod of the present invention adds mesoporous material with mesoporous pore volume on the basis of activated carbon, thereby increasing the pore volume that can accommodate more macromolecular organic matter, which apparently shows that the carbon rod has a longer life and more superior performance in qualified COD removal.

[0031] In a preferred embodiment, the following components are included, by weight: 15-30 parts of ultra-high molecular weight polyethylene, 10-15 parts of low-density polyethylene, 30-70 parts of activated carbon, 10-20 parts of mesoporous material and 0.1-2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

[0032] In other preferred embodiments, by mass, the ultra-high molecular weight polyethylene can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts. The low density polyethylene can be 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts, 19 parts. The activated carbon can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts. The mesoporous material can be 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts, 19 parts, 21 parts, 23 parts, 25 parts. The pore former can be 0.1 part, 0.3 part, 0.5 part, 0.7 part, 0.9 part, 1.1 part, 1.5 part, 2 parts, 2.5 parts, 32 parts. The addition of the pore former can further improve the porosity of the carbon rod after sintering and increase the number of micropores and mesopores of the carbon rod.

[0033] In a preferred embodiment, the average molecular weight of the ultra-high molecular weight polyethylene is 3×10 6 g / mol~6×10 6 g / mol, preferably 3×10 6 g / mol, 3.5×10 6 g / mol, 4×10 6 g / mol, 4.5×10 6 g / mol, 5×10 6 g / mol, 5.5×10 6 g / mol, 6×10 6 g / mol, and in a further preferred embodiment, it can be a mixture of the above ultra-high molecular weight polyethylenes with different molecular weights.

[0034] In a preferred embodiment, the average particle size of the ultra-high molecular weight polyethylene may be 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, or 200 μm. In a further preferred embodiment, the ultra-high molecular weight polyethylene may be a mixture of the above ultra-high molecular weight polyethylenes of different particle sizes.

[0035] In a preferred embodiment, the viscosity of the ultra-high molecular weight polyethylene is 1500 mL / g to 3500 mL / g, specifically 1500 mL / g, 2000 mL / g, 2500 mL / g, 3000 mL / g, 3500 mL / g, etc.

[0036] In a preferred embodiment, the density of the low-density polyethylene is 0.85 g / cm 3 ~0.95g / cm 3 In a further preferred embodiment, the density of the low-density polyethylene can be 0.85 g / cm 3 , 0.87g / cm 3 , 0.89g / cm 3 、0.91g / cm 3 , 0.93g / cm 3 , 0.95g / cm 3 wait.

[0037] In a preferred embodiment, the average particle size of the low-density polyethylene may be 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm. In a further preferred embodiment, the low-density polyethylene may be a mixture of the above low-density polyethylenes of different particle sizes.

[0038] In a preferred embodiment, the melt index of low-density polyethylene is 0.1 g / 10min to 5 g / 10min. Melt index is also called melt flow rate. Specifically, melt index refers to the mass of thermoplastic plastics passing through a standard die every 10 minutes under a certain temperature and load, and the unit is g / 10 minutes. Generally speaking, the larger the melt index, the better the fluidity of the plastic. Preferably, it can be 0.1 g / 10min, 1 g / 10min, 2 g / 10min, 3 g / 10min, 4 g / 10min, and 5 g / 10min.

[0039] In a preferred embodiment, the iodine value of the activated carbon is greater than or equal to 900. The iodine value of the activated carbon can be 900, 950, 1000, 1050, 1100, 1150, 1200, etc.

[0040] In a preferred embodiment, the particle size of the activated carbon is 80-325 mesh, and can be 80-120 mesh, 80-150 mesh, 80-200 mesh, 80-300 mesh, or a mixture of activated carbons of the above different mesh ranges.

[0041] In a preferred embodiment, the activated carbon is one or more of coconut shell activated carbon, bamboo activated carbon, fruit shell wood activated carbon, and biomass activated carbon. The embodiments of the present invention can use different sources of activated carbon raw materials, not limited to high-quality activated carbon, and through improvements in formulation and preparation methods, the sintered carbon rods can have excellent performance, reduce the difficulty of mass production process, thereby reducing production costs and enabling more widespread applications.

[0042] In a preferred embodiment, the particle size of the mesoporous material is greater than or equal to 200 mesh. Optionally, the particle size of the mesoporous material may be 200 mesh-250 mesh, 200 mesh-325 mesh, 200 mesh-400 mesh, or other sizes.

[0043] In a preferred embodiment, the methylene blue value of the mesoporous material is greater than or equal to 8 mL / g. The methylene blue value refers to the amount of methylene blue adsorbed by a unit mass of the adsorbent material under specific conditions, and is mainly used to characterize the adsorption performance of the material, especially the adsorption capacity for macromolecular substances. Preferably, the methylene blue value of the mesoporous material can be 8 mL / g, 8.5 mL / g, 9 mL / g, 9.5 mL / g, 10 mL / g, or others.

[0044] In a preferred embodiment, the mesopore volume of the mesoporous material accounts for 40%-80% of the total pore volume. Preferably, the proportion of the mesopore volume to the total pore volume can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%.

[0045] In a preferred embodiment, the mesoporous material is one or more of wood activated carbon, zeolite powder, molecular sieve, and diatomaceous earth.

[0046] In a preferred embodiment, the pore-forming agent is hydroxyapatite or ammonium bicarbonate; or a mixture of hydroxyapatite and ammonium bicarbonate in a ratio of (1-3): 1. The ratio of hydroxyapatite to ammonium bicarbonate can be 1:1, 2:1 or 3:1, or other specific ratios within the above range.

[0047] Please refer to Figure 1 The embodiment of the present invention further provides a method for preparing a carbon rod with a long COD removal life, which is used to prepare any of the above carbon rods with a long COD removal life, and is characterized in that it comprises the following steps:

[0048] Step S1: Mix the low-density polyethylene 1 and the mesoporous material 2 in proportion, place them in a stirrer and stir for 5-60 minutes, heat to 20°C-80°C, and stir at a speed of 150-500r / min to obtain a mixed material A; in this step, the low-density polyethylene 1 and the mesoporous material 2 can be heated by water bath heating or oil bath heating. Mixing under appropriate conditions can make the low-density polyethylene 1 and the mesoporous material 2 more evenly combined, and the powder is distributed in granular form without being compacted, which effectively solves the problem of insufficient strength of the mesoporous material itself and low strength of the subsequently fired carbon rod.

[0049] Step S2: mixing the ultra-high molecular weight polyethylene 3 and the activated carbon 4 in proportion, placing in a stirrer and stirring for 5-60 minutes at a stirring speed of 150-500 r / min to obtain a mixed material B;

[0050] Step S3: Mixing the mixed material A and the mixed material B, placing them in a stirrer and stirring them for 5-60 min at a stirring speed of 150-500 r / min to obtain a carbon rod mixed material;

[0051] Step S4: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 100° C.-350° C. for 30 min-3 h, and cool it to room temperature after baking;

[0052] Step S5: demoulding and taking out the carbon rod, and cutting it into required size.

[0053] In a preferred embodiment, before the mixing step of step S1 and step S2, the ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material are pre-dried, and the pre-drying process includes the following steps:

[0054] Step S10: placing ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material in containers of a drying device respectively;

[0055] Step S11: Start the drying equipment, the drying temperature is 50°C-150°C, the drying time is 2-5h, and the drying is completed and cooled to room temperature.

[0056] In order to better illustrate the scheme of the present invention, the following are specific embodiments.

[0057] Example 1

[0058] The formula of the carbon rod is as follows: by mass: 10 parts of ultra-high molecular weight polyethylene, 5 parts of low-density polyethylene, 25 parts of activated carbon, 10 parts of mesoporous material and 1 part of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0059] Preparation method:

[0060] Step S1: low-density polyethylene and mesoporous material are mixed in proportion, placed in a stirrer and stirred for 15 minutes at a stirring speed of 200 r / min to obtain a mixed material A;

[0061] Step S2: mixing ultra-high molecular weight polyethylene and activated carbon in proportion, placing in a stirrer and stirring for 15 minutes at a stirring speed of 250 r / min to obtain a mixed material B;

[0062] Step S3: Mixing the mixed material A and the mixed material B, placing them in a stirrer and stirring them for 20 minutes at a stirring speed of 250 r / min to obtain a carbon rod mixed material;

[0063] Step S4: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 200° C. for 2 hours, and cool it to room temperature after baking;

[0064] Step S5: The carbon rod is removed from the mold and cut into the size of outer φ30 mm×inner φ10 mm×length 300 mm.

[0065] Example 2

[0066] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0067] Preparation method: Same as Example 1.

[0068] Example 3

[0069] The formula of the carbon rod is as follows: by mass: 35 parts of ultra-high molecular weight polyethylene, 20 parts of low-density polyethylene, 75 parts of activated carbon, 25 parts of mesoporous material and 3 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0070] Preparation method: Same as Example 1.

[0071] Example 4

[0072] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 150μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0073] Preparation method: Same as Example 1.

[0074] Example 5

[0075] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 50μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0076] Preparation method: Same as Example 1.

[0077] Example 6

[0078] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is a mixture of hydroxyapatite and ammonium hydrogen carbonate in a ratio of 2:1, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0079] Preparation method: Same as Example 1.

[0080] Example 7

[0081] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 60% of the total pore volume.

[0082] Preparation method: Same as Example 1.

[0083] Comparative Example 1

[0084] The formula of the carbon rod is the same as that of Example 2.

[0085] Preparation method:

[0086] Step S1: ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material are mixed in proportion, placed in a stirrer and stirred for 20 minutes at a stirring speed of 250 r / min to obtain a carbon rod mixture;

[0087] Step S2: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 200° C. for 2 hours, and cool it to room temperature after baking;

[0088] Step S3: The carbon rod is removed from the mold and cut into the size of outer φ30 mm×inner φ10 mm×length 300 mm.

[0089] Comparative Example 2

[0090] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 0 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0091] Preparation method: Same as Example 1.

[0092] Comparative Example 3

[0093] The formula of the carbon rod is calculated by mass: 0 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0094] Preparation method: Same as Example 1.

[0095] Comparative Example 4

[0096] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 150μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0097] Preparation method: Same as Example 1.

[0098] Comparative Example 5

[0099] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 300μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the pore-forming agent is hydroxyapatite, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0100] Preparation method: Same as Example 1.

[0101] Comparative Example 6

[0102] The formula of the carbon rod is as follows: by mass: 20 parts of ultra-high molecular weight polyethylene, 15 parts of low-density polyethylene, 50 parts of activated carbon, 15 parts of mesoporous material and 0 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 120μm, the average particle size of the low-density polyethylene is 80μm, the activated carbon is coconut shell activated carbon, the iodine value of the activated carbon is 1000, the mesh number of the activated carbon is 80-200 mesh, the mesoporous material is wood activated carbon, and the mesoporous pore volume accounts for 40% of the total pore volume.

[0103] Preparation method: Same as Example 1.

[0104] Comparative Example 7

[0105] The formula of the carbon rod is the same as that in Example 2.

[0106] Preparation method:

[0107] Step S1: low-density polyethylene and mesoporous material are mixed in proportion, placed in a stirrer and stirred for 15 minutes at a stirring speed of 200 r / min to obtain a mixed material A;

[0108] Step S2: mixing ultra-high molecular weight polyethylene and activated carbon in proportion, placing in a stirrer and stirring for 15 minutes at a stirring speed of 250 r / min to obtain a mixed material B;

[0109] Step S3: Mixing the mixed material A and the mixed material B, placing them in a stirrer and stirring them for 20 minutes at a stirring speed of 250 r / min to obtain a carbon rod mixed material;

[0110] Step S4: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 450° C. for 2 hours, and cool it to room temperature after baking;

[0111] Step S5: The carbon rod is removed from the mold and cut into the size of outer φ30 mm×inner φ10 mm×length 300 mm.

[0112] Comparative Example 8

[0113] Finished activated carbon rod filter materials purchased on the market.

[0114] The carbon rods of Examples 1-7 and Comparative Examples 1-8 were tested for performance:

[0115] (1) Residual chlorine removal rate test: refer to the relevant test methods in the national standard GB / T5750 to test the residual chlorine content; refer to the national standard GB / T30307 to confirm the test conditions, which are divided into full-process spike flow and tap water point spike filtration, with a standard flow rate of 2L / min.

[0116] (2) Oxygen consumption removal rate test: Refer to the relevant test methods in the national standard GB / T5750 to test the COD content; refer to the national standard GB / T30307 to confirm the test conditions, which are divided into full-process spike flow and tap water point spike filtration, with a standard flow rate of 2L / min.

[0117] (3) Structural strength test (crushing force test): Take 30mm from the center of the sintered carbon rod and place it horizontally on the operating table. Use a universal testing machine to automatically test the crushing force.

[0118] The following are the specific test results.

[0119] Table 1 Residual chlorine removal rate test results (full residual chlorine spike flow)

[0120]

[0121]

[0122] Table 2 Residual chlorine removal rate test results (tap water flow, point spike residual chlorine test)

[0123]

[0124]

[0125] Table 3 COD removal rate test results (full COD spike flow)

[0126]

[0127]

[0128] Table 4 COD removal rate test results (tap water flow, point spike COD test)

[0129]

[0130] As can be seen from Table 1-Table 4, the carbon rods of Examples 1-7 have excellent performance in removing residual chlorine and COD, and have a long life span for effectively removing pollutants. Furthermore, the method of direct mixing of all components adopted in Comparative Example 1 is not classified and mixed. Comparison of Comparative Example 1 and Example 2 shows that the performance and life span of the carbon rods in Comparative Example 1 in removing residual chlorine and COD are worse than those in Example 2. Comparison of Comparative Example 2 and Example 2 shows that the performance and life span of the carbon rods without adding low-density polyethylene to remove residual chlorine and COD are significantly reduced. Comparison of Comparative Example 3 and Example 2 shows that the performance and life span of the carbon rods without adding ultra-high molecular weight polyethylene to remove residual chlorine and COD are significantly reduced. Comparison of Comparative Example 4 and Example 2 shows that when low-density polyethylene with a larger particle size is used, the performance and life span of the carbon rods in removing residual chlorine and COD will be reduced to a certain extent. Comparison of Comparative Example 5 and Example 2 shows that when ultra-high molecular weight polyethylene with a larger particle size is used, the performance and life span of the carbon rods in removing residual chlorine and COD will be reduced to a certain extent. Comparison of Comparative Example 6 and Example 2 shows that when no pore-forming agent is added, the performance and life of the carbon rod in removing residual chlorine and COD will be reduced to a certain extent. In the preparation method of Comparative Example 7, the sintering temperature is too high, resulting in a decrease in porosity and pore size. Comparison of Comparative Example 7 and Example 2 shows that the performance and life of the carbon rod in Comparative Example 7 in removing residual chlorine and COD will be significantly reduced. Comparison of Comparative Example 8 is an ordinary activated carbon rod filter material purchased on the market. Comparison of Comparative Example 8 and Examples 1-7 shows that the performance and life of the carbon rod provided by the present invention in removing residual chlorine and COD are superior to those of ordinary activated carbon rod filter materials on the market.

[0131] Table 5 Crushing force test results

[0132]

[0133] Table 5 shows the results of the crushing force test of Examples 1-7 and Comparative Examples 1-8. By comparing Examples 1-7 with Comparative Example 8, it can be seen that the carbon rods prepared by the scheme of the present invention have similar strength to ordinary activated carbon rod filter materials on the market, and can meet the needs of transportation and use. By comparing Example 2 with Comparative Example 2, it can be seen that the strength of the prepared carbon rods is significantly reduced due to the lack of low-density polyethylene; by comparing Example 2 with Comparative Example 3, it can be seen that the strength of the carbon rods is also significantly reduced without the addition of ultra-high molecular weight polyethylene. In Example 7, due to the excessively high sintering temperature, the carbon rods become brittle and the strength is significantly reduced.

[0134] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A carbon rod with a long COD removal life, characterized in that: The invention comprises the following components by weight: 10-35 parts of ultra-high molecular weight polyethylene, 5-20 parts of low-density polyethylene, 25-75 parts of activated carbon, 5-25 parts of mesoporous material and 0.1-3 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

2. The carbon rod with a long COD removal life according to claim 1, characterized in that: The invention comprises the following components in parts by mass: 15-30 parts of ultra-high molecular weight polyethylene, 10-15 parts of low-density polyethylene, 30-70 parts of activated carbon, 10-20 parts of mesoporous material and 0.1-2 parts of pore-forming agent, wherein the average particle size of the ultra-high molecular weight polyethylene is 100-200 μm, and the average particle size of the low-density polyethylene is less than or equal to 100 μm.

3. The carbon rod with a long COD removal life according to claim 1, characterized in that: The viscosity of ultra-high molecular weight polyethylene is 1500mL / g~3500mL / g, and the melt index of low density polyethylene is 0.1g / 10min~5g / 10min.

4. The carbon rod with a long COD removal life according to claim 1, characterized in that: The iodine value of the activated carbon is greater than or equal to 900, and the particle size of the activated carbon is 80 meshes to 325 meshes.

5. The carbon rod with a long COD removal life as claimed in claim 4, characterized in that: The activated carbon is one or more of coconut shell activated carbon, bamboo activated carbon, fruit shell wood activated carbon, and biomass activated carbon.

6. The carbon rod with a long COD removal life according to claim 1, characterized in that: The particle size of the mesoporous material is greater than or equal to 200 meshes, the methylene blue value is greater than or equal to 8 mL / g, and the mesopore volume of the mesoporous material accounts for 40%-80% of the total pore volume.

7. The carbon rod with a long COD removal life according to claim 6, characterized in that: The mesoporous material is one or more of wood activated carbon, zeolite powder, molecular sieve and diatomaceous earth.

8. The carbon rod with a long COD removal life according to claim 1, characterized in that: The pore-forming agent is hydroxyapatite or ammonium hydrogen carbonate; or a mixture of hydroxyapatite and ammonium hydrogen carbonate in a ratio of (1-3):

1.

9. A method for preparing a carbon rod with a long COD removal life, for preparing a carbon rod with a long COD removal life as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1: low-density polyethylene and mesoporous material are mixed in proportion, placed in a stirrer and stirred for 5-60 minutes, heated to 20° C.-80° C., and stirred at a speed of 150-500 r / min to obtain a mixed material A; Step S2: mixing ultra-high molecular weight polyethylene and activated carbon in proportion, placing in a stirrer and stirring for 5-60 minutes at a stirring speed of 150-500 r / min to obtain a mixed material B; Step S3: Mixing the mixed material A and the mixed material B, placing them in a stirrer and stirring them for 5-60 min at a stirring speed of 150-500 r / min to obtain a carbon rod mixed material; Step S4: Fill the carbon rod mixture into a sintering mold and compact the carbon rod mixture, bake it at a sintering temperature of 100° C.-350° C. for 30 min-3 h, and cool it to room temperature after baking; Step S5: demoulding and taking out the carbon rod, and cutting it into required size.

10. The method for preparing a carbon rod with a long COD removal life according to claim 9, characterized in that: Before the mixing step of step S1 and step S2, the ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material are pre-dried, and the pre-drying process includes the following steps: Step S10: placing ultra-high molecular weight polyethylene, low-density polyethylene, activated carbon and mesoporous material in containers of a drying device respectively; Step S11: Start the drying equipment, the drying temperature is 100°C-150°C, the drying time is 2-5 hours, and the drying is completed and cooled to room temperature.